Association between hyperglycemia and adverse clinical outcomes of sepsis patients with diabetes - Lin, Shan; Lai, Dingfeng; He, Wanmei (Frontiers in Endocrinology, 2023)
Background: Hyperglycemia is one of the poor prognostic factors in critical ill sepsis patients with diabetes. We aimed to assess the interaction between admission glucose level and clinical endpoints in sepsis patients with diabetes admitted in the intensive care unit (ICU). Methods: Data from the Medical Information Mart Intensive Care III database were used in this study. The study primary endpoint was 28-day mortality after ICU admission. Multivariate Cox regression models were used to explore the association between admission glucose level and the primary endpoint. Results: We included 3,500 sepsis patients with diabetes. Of participants with no hyperglycemia, mild hyperglycemia, and severe hyperglycemia, no differences were evident in hospital mortality, ICU mortality, or 28-day mortality (all P >0.05). The multivariable Cox regression analysis demonstrated that severe hyperglycemia did not increase the risk of 28-day mortality (hazard ratio [HR]=1.06, 95% confidence interval [CI]: 0.86–1.31, P=0.5880). Threshold effects analysis identified the inflection points for 28-day mortality as 110 mg/dl and 240 mg/dl. The HRs for 28-day mortality were 0.980 in the <110 mg/dl and 1.008 in the >240 mg/dl. A short-term survival advantage was observed in the 110–240 mg/dl group compared with that in the <110 mg/dl group; meanwhile, no adverse hazard was detected in the >240 mg/dl group. In the stratified analyses, the association effect between the three glucose groups (<110 mg/dl, 110–240 mg/dl, and ≥240 mg/dl) and 28-day mortality was consistent in terms of different sequential organ failure assessment (SOFA) scores and infection sites. The 28-day mortality of the 110–240 mg/dl group with a SOFA score of ≥10 was lower than that of the <110 mg/dl group (HR=0.61, 95% CI: 0.38–0.98). Conclusion: Admission hyperglycemia was not a risk factor for short-term prognosis in critical ill sepsis patients with diabetes; a lower admission blood glucose level was associated with increased risk of poor prognosis. The potential benefit of higher admission glucose level on 28-day mortality in patients with a more severe condition remains a concern.